Quantitative index calculated by 99mTc-GSA scintigraphy - Yoshida, Morikatsu; Shiraishi, Shinya; Tsuda, Noriko; Sakamoto, Fumi; Tomiguchi, Seiji; Yamashita, Yasuyuki (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
99mTc-galactosyl human serum albumin (GSA) scintigraphy is useful to evaluate hepatic function and hepatic functional reserve. A reliable SPECT and CT integrated system is now commercially available. Using this system, we can obtain 99mTc-GSA SPECT/CT fused imaging with a small registration error. Therefore, the 99mTc-GSA scintigraphy techniques prove more useful in clinical practice than have been previously reported. In the latest Annals of Surgical Oncology on Oct 2014, the uptake index (UI) values calculated from 99mTc-GSA scintigraphy are reported to be useful for predicting the functional reserve of the future remnant liver. In this paper, we describe the usefulness of 99mTc-GSA scintigraphy as well as some cautions that are necessary as regards using the system.